2017
DOI: 10.1108/ijsms-05-2017-090
|View full text |Cite
|
Sign up to set email alerts
|

Do college athletics marketers convert social media growth into ticket sales?

Abstract: Purpose The purpose of this paper is to examine the relationship between growth in social media engagement, as defined by annual percentage increase in Facebook Likes and Twitter Followers, of US college athletics departments and outcome metrics of attendance and ticket revenue. Design/methodology/approach Regression models were developed to determine the amount of variance in dependent variables (attendance and ticket revenue) could be explained by several independent variables, including team success, team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Few studies connecting Twitter and sport have attempted to assess the value of Twitter hashtags as a marketing and sales tool. Popp and McEvoy (2014) found university athletic department so far unable to demonstrate the financial impact of social media on their bottom line. Studies by Ciuffo et al (2014), and Abeza and O'Reilly (2014) demonstrated that Twitter is less effective in sports marketing efforts than other forms of engagement, whereas Watkins (2014) found Twitter had a positive impact on brand equity for NBA fans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies connecting Twitter and sport have attempted to assess the value of Twitter hashtags as a marketing and sales tool. Popp and McEvoy (2014) found university athletic department so far unable to demonstrate the financial impact of social media on their bottom line. Studies by Ciuffo et al (2014), and Abeza and O'Reilly (2014) demonstrated that Twitter is less effective in sports marketing efforts than other forms of engagement, whereas Watkins (2014) found Twitter had a positive impact on brand equity for NBA fans.…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of social media's use as marketing and sales tools suggest it can help increase fan engagement (Tomko, 2011) and sell tickets (Steinbach, 2010). However, analyses of sport social media and sales demonstrate that claim has so far been difficult to demonstrate empirically (Popp and McEvoy, 2014). The non-curated construct of Twitter means that marketers need to be mindful of efforts by advocates to 'hijack' their marketing hashtags for completely different purposes (Fathi, 2009), or create counter-marketing hashtags to combat their stated business goals (Burton et al, 2013).…”
Section: Twitter Hashtagsmentioning
confidence: 99%
See 1 more Smart Citation
“…of comments, No. of shares Facebook Popp et al ( 2017 ) Quantitative Metrics No. of Facebook Followers, No.…”
Section: Social Media Engagement: Areas Of Investigationmentioning
confidence: 99%
“…However, little is known about how social networking sites impact purchases in sport (Hong and Rhee, 2016). In one study, Popp et al (2017) determined the number of Facebook page likes and Twitter followers did not increase ticket revenues or attendance, thus suggesting it might not be an effective sales tool. Conversely, other studies advocate that teams with higher revenues have more Facebook fans (Parganas et al, 2017), and teams with more Facebook fans have higher operating incomes and attendance (Achen, 2015), which provide correlational evidence that a relationship exists, but do not try to determine if consumer behavior is impacted by interacting with teams on social networks.…”
Section: Measuring Social Media Marketingmentioning
confidence: 99%